A novel series of 11-O-carbamoyl-3-O-descladinosyl clarithromycin derivatives bearing 1, 2, 3-triazole group: Design, synthesis and antibacterial evaluation. Issue 2 (15th January 2020) - Teng, Yuetai; Qin, Yinhui; Song, Di; Liu, Xingbang; Ma, Yingang; Zhang, Panpan; Ma, Shutao
Graphical abstract: Highlights: Novel 11- O -carbamoyl-3- O -descladinosyl clarithromycin derivatives were synthesized and evaluated. Some of them showed effective activity against both susceptible and resistant strains. Compound 13d and 13g exhibited prominent antibacterial activity. Abstract: A series of novel 11- O -carbamoyl-3- O -descladinosyl clarithromycin derivatives bearing the 1, 2, 3-triazole group were designed, synthesized, and evaluated for their in vitro antibacterial activity. The antibacterial results indicated that most of the target compounds not only increased their activity against resistant bacterial strains, but also partially retained the activity against sensitive bacterial strains compared with clarithromycin. Among them, 13d had the best antibacterial activity against resistant strains, including Streptococcus pneumoniae B1 expressing the erm B gene (16 µg/mL), Streptococcus pneumoniae AB11 expressing the mef A and erm B genes (16 µg/mL) and Streptococcus pyogenes R1 (16 µg/mL), showing >16, 8 and 16-fold higher activity than that of CAM, respectively. Moreover, 13d and 13g exhibited the best antibacterial activity against sensitive bacterial strains, including Staphylococcus aureus ATCC25923 (4 µg/mL) and Bacillus Subtilis ATCC9372 (1 µg/mL). The MBC results showed that the most promising compounds 13d and 13g exhibited antibacterial activity through bacteriostatic mechanism, while the time-kill kinetic experiment revealed bactericidal kinetics of 13g from microscopic point of view. In vitro antibacterial experiments and molecular docking results further confirmed that it was feasible to our initial design strategy by modifying the C-3 and C-11 positions of clarithromycin to increase the activity against resistant bacteria.